The changing geography of Christianity in China, 1918-2004. Issue 4 (1st October 2016) - Tong, James W.
ABSTRACT: Using systematic provincial level data on the number of Protestant Christians in 1918, 1949, 1997 and 2004, and those on Christian religious venues in 1979, 1997 and 2004, this article analyses changes in the coastal dominance, urban primacy and spatial diffusion of Christian communities in China. Six decades of communist rule eroded the missionary legacy, as Christian communities spread to China's interior provinces and the rural hinterland, and became more widespread in China by 2004, with the sharpest decline in metropolitan cities and in the Guangdong province, and the fastest growth in the interior and northeast provinces. Ethnographies and case studies suggest that these developments may have resulted from the diminution of the missionary legacy, the relative decline of the institutional churches versus indigenous congregations, the replacement of an anti-state old guard by more pragmatic and compliant church leaders, the rise of the charismatic Pentecostal movement and the evangelism of a new breed of Christian entrepreneurs. These religious sociological factors may have also interacted with urbanisation and national and local religious policy to produce permutations in the distribution of Christian communities which can only be thoroughly analysed through systematic data-based research.